Endoscopic Management of Benign Gallbladder Diseases - Ji, Yimei; Huang, Weirong; Guo, Jiefang; Hu, Bing (Turkish Journal of Gastroenterology, 2024)
Abstract Acute cholecystitis, cholelithiasis, and gallbladder polyps represent the most gallbladder benign diseases. Endoscopic approaches for the management of these diseases were an alternative to standard laparoscopic cholecystectomy. These endoscopic approaches include transpapillary approaches via endoscopic retrograde cholangiopancreatography, transmural access approaches via endoscopic ultrasound, and endoscopic surgical approaches using natural orifice transluminal endoscopic surgery approaches. However, it’s still uncertain which approach is associated with the superior clinical outcomes due to the lack of high-level evidence. Our review provides new insight into the endoscopic approaches for the management of gallbladder benign diseases, with the latest evidence included. Cite this article as: Ji Y, Huang W, Guo J, Hu B. Endoscopic management of gallbladder benign diseases. Turk J Gastroenterol.2024;35(9):681-689.